Rancang Bangun Sistem Informasi Geografis Rekomendasi Cagar Budaya Menggunakan Metode Analytic Hierarchy Process - Nicolas Evander Suhandi; Kristoko Dwi Hartomo; Penidas Fiodinggo Tanaem (Maranatha University Press, 2020)
Salatiga City is a town located in the province of Central Java. In this town, there can be found many cultural heritage buildings that were built in the mid-18th century to 1940. Potential visitors would increase easier if a geographic information system is built. Tourists who visit can access the website to select or search for cultural heritage that they want to visit, therefore the availability of a geographic information system that provides information and data on the location of cultural heritage in digital maps is needed. The system must also consider aspects of the cultural heritage rating, the price of admission, and the condition of the cultural heritage to provide recommendations on which cultural heritage to be visited. Therefore the geographic information system of cultural heritage recommendations uses the analytical hierarchy process (AHP) method which can calculate multi- criteria, multi alternatives, and provides cultural heritage recommendations. This system combines geographic information system as a provider of cultural heritage information and AHP decision support system to assist tourists in choosing cultural heritage.